Perspectives of WIC Staff Regarding Physical Activity Levels and Behaviors of Latino Preschool Children - Lindsay, Ana Cristina; Greaney, Mary; Salkeld, Judith A.; Walsh, Jennifer (International Journal of Child Health and Nutrition, 2015)
Background: Racial and ethnic disparities in physical activity (PA) are evident, with non-Hispanic Black and Mexican American children engaging in less vigorous activity than non-Hispanic White children. Collaborating with public health programs serving at-risk populations, such as the WIC program may be an effective way to promote the development of healthful PA behaviors among low-income preschool children and families. This paper explores WIC staff perceptions, attitudes, barriers, and facilitators related to PA levels and behaviors among low-income Latino preschool children and families, as well as the role the WIC program may play in promoting PA among low-income populations. Methods: A qualitative study was conducted with a sample of WIC staff in the State of Rhode Island (RI), Northeast United States. Individual, semi-structured interviews were carried out with 21 WIC staff working directly with Latino clients enrolled in the WIC program. Thematic content analysis was used. Results: The majority of WIC staff reported their Latino clients facing many barriers that limit their ability to be physically active, including busy and multiple shift schedules, lack of access to safe outdoor spaces, financial constraints to attending programs and recreational facilities, lack of transportation getting to safe outdoor spaces and facilities, etc. WIC staff identified several ways that the WIC program could increase the promotion PA among Latino families including partnering with local organizations such as the YMCA, Boys and Girls Club to provide increased access and opportunities for PA among low-income, Latino families. Conclusions: Study findings add to the existing literature suggesting that the WIC program is an important venue for educating low-income, Latino children and families about the importance of establishing early healthy PA habits within the context of overall health and development. Findings also highlight the need for a continuing effort to integrate the promotion of PA as part of the WIC program. In addition, findings highlight WIC staff desire for additional training and resources in promotion of PA.